Cognitive styles of consumer initiators - Foxall, Gordon R. (Technovation)
Foxall's study of the Kirton Adaptor-Innovator theory following work in three organizations concerned with food brands and products and two with the use of computer software suggests a more complex psychographic composition of consumer innovator segments than has generally been appreciated.